Socialization Strategy Of Posyandu Dahlia Cadres In Order To Reduce Infant Malnu-trition In The Age Range Of 0-9 Months In Heramkota District, Jayapura - Mesakh Mirin (Green Publisher Indonesia, 2024)
This research focuses on the socialization of health communication carried out by Posyandu Dahlia Heram District cadres in reducing the number of cases of malnutrition in infants aged 0-9 months. Using descriptive qualitative research and an interpretive paradigm, the author tries to find the strategies used by Posyandu Dahlia cadres when they go to the field to reduce infant mortality. Data sources were obtained through in-depth interviews with seven informants as wel as from valid internet reference sources, books and documentation by the authors in the field directly. This study found that Huge Rank's Health Communication Theory did not apply al of the techniques by Posyandu Dahlia Cadres. Only a few of the downplay and intensive techniques were used by informants if they were suitable for application when socializing or carrying out work program activities from the posyandu.